Analysis Of Poverty Treatment Programs Of The Government And Find Matra To Community Welfare (Case Study of Business Facilities for Poor Female Heads of Households in Perak Subdistrict) - Sa’adah, Lailatus; Sa’adah, Rizky Amaliyatuz (IJOSMAS, 2021)
The purpose of this research is to find out whether the program of intertwining poor families for women households (KRTP) is very influential in shaping the economy of women in Perak sub-district. The object of this research was widows who received the Jalin Matra program assistance in Perak Subdistrict, out of 5 villages, with a total of 46 people. This study of this research was descriptive qualitative, the reseacrh approach carried out by looking directly at the problems that occurred in the field. In qualitative research, the methods used are interviews, observation and use of documents. Widows who receive business capital assistance worth Rp. 750,000 in the form of business necessities. On average, people who received Jalin Matra assistance had an increase in terms of increasing income to meet basic needs, school fees and other social needs without having to be in debt to other people.